EFEKTIVITAS E-LEARNING SEBAGAI MEDIA PEMBELAJARAN PADA MATA KULIAH BAHASA INGGRIS DI POLITEKNIK NEGERI JAKARTA - Nia Rismawati; Suci Widyorini; Sugiyarto; Nina Sulistyowati (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2022)
The Covid-19 pandemic that hit Indonesia caused the temporary suspension of all learning activities. This requires higher education units to utilize science and technology effectively and efficiently. One of the learning media that can be used is e-learning. However, the application of online lectures through e-learning is a big question mark regarding the effectiveness of its use. The purpose of this study was to determine the effectiveness of using e-learning to improve English language skills in the era of the Covid 19 pandemic. This research is an experimental study conducted at the Jakarta State Polytechnic PSDKU Demak. The instrument used in this research is in the form of pre-test and post-test questions. Analysis of the data used in this study is the N-Gain and the N-Gain difference test using the t-test to determine the effectiveness of the use of e-learning. Based on the results of the effectiveness test of using e-learning, it can be concluded that from the effectiveness test in the experimental class, the criteria that e-learning is quite effective and significant in improving English language skills in the Covid 19 pandemic era.